Analysis of the impact of ownership characteristics on the capital structure and business success of companies in the Balkan beverage industry - Teodora Tica (Anali Ekonomskog fakulteta u Subotici, 2022)
The aim of the research is to present the influence of ownership characteristics on the capital structure and business success of companies theoretically and empirically. The research was conducted on a sample of 96 active companies operating within the beverage industry in the Balkan countries in 2019. Empirical research was carried out by using one-factor analysis of variance (ANOVA). The paper presents two models. One is related to the analysis of the effects of foreign ownership to profitability, liquidity, asset and capital structure, while the other model analyses the impact of ownership concentration on the same variables. The results of the models evaluation confirmed the existence of a statistically significant difference only between foreign ownership and liquidity. In this regard, the ownership characteristics are considered not to affect the business success of the sampled companies, but rather, the performance is affected by other internal and external factors.